(untitled) (KULT_online, 2012)
Edited by Christian Meyer and Felix Girke, The Rhetorical Emergence of Culture is the fourth volume in the interdisciplinary series Studies in Rhetoric and Culture, which has fostered the dialogue between rhetoric and anthropology since 2009. Arranged into three sections on intersubjectivity, emergence, and agency, fifteen articles examine the cultural foundations of rhetoric and the rhetorical foundations of culture. Contributors hail mainly from anthropology and rhetoric, but also from communication studies, cognitive studies, linguistics, and philology. Hence the topics range from the ancient ideal of the orator and early modern Jesuit rhetoric in Goa to Internet forums for Russian migrants to the United States and the connections between architecture and public speech in New Guinea. Whilst some of the contributions are kept very general and others are in the main designed for specialists, the volume represents an important building block in bridging anthropological and rhetorical research. What is more, the thesis of the interconnection of rhetoric and culture is relevant for fundamental research in cultural studies.